An Improved Bus Connected PV System For Marine Ships - Dhiman, Sourav (My University, 2018)
Photovoltaic (PV) systems converts the solar energy falling on them directly into electricity. In this thesis, an improved PV system connected with the electricity distribution system of marine ships is purposed. The proposed methodology will track the maximum power point (MPP) of PV array using hybrid MPPT technique and flyback DC-DC converter. The tracked maximum power is then converted into 3-phase AC power using a full bridge voltage source inverter controlled by space vector pulse width modulation (SVPWM) technique. This 3- phase power will feed the local load and the excess AC power is transmitted into the electricity distribution system of ship. Moreover, the system includes protection from different faulty conditions. As well, the necessary steps and key components needed to design and build an efficient, reliable and protective photovoltaic system are examined.
Keywords: Photovoltaic; SVPWM; MPPT; EDS; duty cycle; ship's bus